Appropriate supply of irrigation and nitrogen produced higher yields of cherry tomatoes - Cai, Zelin; Zhang, Mengchi; Xie, Jiarui; Kong, Tingting; Zhang, Yuxuan; Zhang, Yuxuan; He, Zhihao; Zhang, Zhi (International Journal of Agricultural and Biological Engineering, 2024)
Accurate irrigation and nitrogen application are essential for promoting the growth and yield of cherry tomatoes. In investigating the effects of irrigation and nitrogen on the growth, photosynthesis, and yield of cherry tomatoes, nine treatments including three levels of both irrigation and nitrogen were conducted over two growing seasons. Transverse stem diameter and horizontal stem diameter had the best performance at the irrigation level of 75% evaporation (Ep), although their responses to nitrogen were different for the two years. Plant height increased with the increase of irrigation and nitrogen. Plant dry matter (PDM) was significantly affected by irrigation and nitrogen interaction. The lowest PDM was found in the highest proportion of root dry matter, which occurred under low nitrogen level. The net photosynthetic rate (Pn) and transpiration rate enhanced with the increase of irrigation. Medium nitrogen showed promotion effect on all photosynthetic parameters in both growing seasons. Six of all fourteen indicators showed significant correlations with yield. Especially, single plant fruit number and PDM in 2018 Fall had significant positive direct effects on yield with the path coefficients of 0.648 and 1.159, while the significant direct path coefficients were 0.362 and 0.294 in Fruit dry matter and Pn for 2019 Spring, respectively. Based on the comprehensive evaluation of growth and yield by TOPSIS, the irrigation level of 75% Ep combined with medium nitrogen application produced higher yields by promoting the growth and photosynthesis of cherry tomatoes. It provides a strategy for water and nitrogen management of cherry tomatoes in Northwest China. Key words: cherry tomatoes; yield; growth; irrigation; nitrogen; path analysisDOI: 10.25165/j.ijabe.20241702.8018Citation: Cai Z L, Zhang M C, Xie J R, Kong T T, Zhang Y X, He Z H, et al. Appropriate supply of irrigation and nitrogenproduced higher yields of cherry tomatoes. Int J Agric & Biol Eng, 2024; 17(2): 149–158.